Regulating the financial sector in the era of globalization : - Mikdashi, Zuhayr (Palgrave Macmillan, 2003)
The world's financial landscape is transforming as economies become increasingly interdependent. InRegulating the Financial Sector in the Era of Globalization, Zuhayr Mikdashi examines the role of public authorities and of business executives in the prevention, moderation, containment and resolution of financial problems. The book features a foreword by William C. Hunter, Senior Vice President and Director of Research at the Federal Reserve Bank of Chicago.